Non-invasive vagus nerve stimulation in anti-inflammatory therapy: mechanistic insights and future perspectives - Liu, Fu-Jun; Wu, Jing; Gong, Li-Jun; Yang, Hong-Shuai; Chen, Huan (Frontiers in Neuroscience, 2024)
Non-invasive vagus nerve stimulation (VNS) represents a transformative approach for managing a broad spectrum of inflammatory and autoimmune conditions, including rheumatoid arthritis and inflammatory bowel disease. This comprehensive review delineates the mechanisms underlying VNS, emphasizing the cholinergic anti-inflammatory pathway, and explores interactions within the neuro-immune and vagus-gut axes based on both clinical outcomes and pre-clinical models. Clinical applications have confirmed the efficacy of VNS in managing specific autoimmune diseases, such as rheumatoid arthritis, and chronic inflammatory conditions like inflammatory bowel disease, showcasing the variability in stimulation parameters and patient responses. Concurrently, pre-clinical studies have provided insights into the potential of VNS in modulating cardiovascular and broader inflammatory responses, paving the way for its translational application in clinical settings. Innovations in non-invasive VNS technology and precision neuromodulation are enhancing its therapeutic potential, making it a viable option for patients who are unresponsive to conventional treatments. Nonetheless, the widespread adoption of this promising therapy is impeded by regulatory challenges, patient compliance issues, and the need for extensive studies on long-term efficacy and safety. Future research directions will focus on refining VNS technology, optimizing treatment parameters, and exploring synergistic effects with other therapeutic modalities, which could revolutionize the management of chronic inflammatory and autoimmune disorders.